INTESTINAL DYSBIOSIS IN CHILDREN WITH FOOD ALLERGY: PATHOGENETIC ASPECTS AND MODERN CORRECTION METHODS - S.G. Makarova; T.E. Borovik ("Paediatrician" Publishers LLC, 2008)
Background paper analyses the role of intestinal micro-flora at the stage of forming immunity, the importance of intestinal microflora abnormalities during the periods of allergic diseases development (primarily food allergies), as well as mechanisms of dysbiosis effect on the allergic processes in child's body. The study discusses the mechanisms of treatment and prevention effect of probiotics for cases of child allergic diseases. The work also specifies modern approaches to correcting dysbiotic abnormalities for children with food allergies, reviews the options of diet and medication treatment of food allergy, suggests a new algorithm of gradual treatment that targets correction of dysbiosis in this patient category. Key words: children, food allergy, dysbiosis, probiotics, prebiotics, diet therapy.